Monitoring Toddler Development Based on Indonesian Health Survey (SKI) 2023 - Russiska, Russiska; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Background: Monitoring toddler development is a crucial aspect of early detection of growth and developmental issues in children. However, its implementation in Indonesia still faces various challenges, such as low parental awareness and limited access to health services. This study aims to identify factors associated with toddler development monitoring based on data from the 2023 Indonesian Health Survey (SKI). Methods: This research used a quantitative approach with a cross-sectional design involving all children aged 0–6 years across Indonesia. Data were collected through standardized questionnaires and structured interviews, and analyzed using simple linear regression to assess the relationship between socioeconomic factors, ownership and use of the Maternal and Child Health (MCH) handbook (KIA Book), and access to community health centers in relation to child development monitoring. Results: The results indicate that the most dominant factor supporting development monitoring is the ownership and use of the MCH handbook, showing a very strong and significant correlation (R = 0.781 and R = 0.788). Easy access to Puskesmas also had a significant effect (R = 0.681). In contrast, economic status showed a weaker and statistically insignificant relationship in most categories. Conclusion: These findings highlight the importance of increasing parental awareness of the MCH handbook and optimizing access to health services to support more effective child development monitoring.